PERANAN KREATIVITAS ANIMATOR DALAM MEMADUKAN 3D MODELING DAN EFEK PARTIKEL DI FILM QODRAT 2 - Adi, Muhammad As Samii Al Adi; Flora Meliana Siahaan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Indonesian film industry has been rapidly developing through digital technology, such as the use of VFX in the film Qodrat 2 (2025). However, academic studies on the creative dimensions of the animators behind it remain very limited.This study aims to analyze how animator creativity is manifested in combining 3D modeling and VFX particle effects, as well as to examine how the application of the 12 Basic Principles of Animation influences the visual quality of the film. This research uses a qualitative approach with a phenomenological method, conducted through indepth interviews with the VFX Supervisor and VFX Artist who were directly involved in the production of Qodrat 2. The findings show that animator creativity is manifested in three main areas: the creation of 3D models with a visually threatening atmosphere, the configuration of particle effects through physics-based simulations and manual control, and the integration of physical realism with deliberate imperfection strategies to create a mystical atmosphere. In addition, the 12 Basic Principles of Animation are strongly confirmed in seven principles, such as Follow Through and Arcs, while the classical principle of Exaggeration is less dominant in the religious horror genre.This study concludes that animator creativity serves as a bridge between technology and visual communication, with the philosophy of invisible VFX as its main orientation.